What Is the Role of AI in Prosthetics and Orthotics? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2016)
The intersection of artificial intelligence (AI) with prosthetics and orthotics is heralding a new era of personalized and highly functional assistive device...
Keywords: AI in Rehabilitation Medicine; Prosthetics; Orthotics; Artificial Intelligence; Machine Learning; Healthcare